Pengembangan Konstruksi Metodologi Hukum Islam bagi Perubahan Masyarakat Indonesia - Karimatul Ummah (Fakultas Hukum Universitas Islam Indonesia, 2004)
In facing the problem of more and more complex life, the Islamic law must be dynamic and actualin order that its role can be maximized both as a guidance controller of the changeof society. In this condition, the effort of developing the methodological construction of Islamic Law is a must, but it uses the frame of its function.